2018
DOI: 10.14203/jissh.v2i0.19
|View full text |Cite
|
Sign up to set email alerts
|

The Making of Indonesian Education: An overview on Empowering Indonesian Teachers

Abstract: Education is one of the fundamental priorities of nation building. For this reason, the Indonesian government continuously seeks to improve the quality of its education. Empowering education can be done using many strategies, such as reforming school curricula or school systems or both. This article approaches the improvement of Indonesian education from a different angle, by considering teachers and the teaching profession. Before proposing an agenda for improving teachers, the article considers two main prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 15 publications
(16 reference statements)
1
34
0
4
Order By: Relevance
“…However, alongside that growth, the quality of its graduates is questionable. It is still a significant issue that new teachers are entering their classrooms feeling unprepared due to some factors such as the absence of induction and inadequate teacher preparation (Tazeen, Rythia, & Heather, 2018;Zulfikar, 2009).…”
Section: Teacher Law and Certificationmentioning
confidence: 99%
“…However, alongside that growth, the quality of its graduates is questionable. It is still a significant issue that new teachers are entering their classrooms feeling unprepared due to some factors such as the absence of induction and inadequate teacher preparation (Tazeen, Rythia, & Heather, 2018;Zulfikar, 2009).…”
Section: Teacher Law and Certificationmentioning
confidence: 99%
“…We share understanding of good learning with prominent figures in the field of education, such as John Dewey, Ira Shor, Paulo Freire and other important figures in the field who believe that effective learning occurs through learner-centred instruction. We refer to Zulfikar's (2009) article in which he argues that Indonesian teachers are not willing to share classroom authority, while the willingness to share authority is a prerequisite for learner-centered instruction. Furthermore, in Zulfikar (2013), we understand that it is difficult to instill progressive ideas to students who hold the doctrine that challenging elders are not appropriate.…”
Section: The Indonesian School Culturesmentioning
confidence: 99%
“…A number of studies have also found that the teachers' lack of pedagogical competence is the major problem in Indonesian English language classroom. As a result, the students failed to understand the lesson (Rido, 2018(Rido, , 2017Rido, Nambiar, Noraini, 2015;Mattarima & Hamdan, 2011;Marcellino, 2009;Zulfikar, 2009;Lie, 2007).…”
Section: Introductionmentioning
confidence: 99%